Pengembangan Bahan Ajar Materi Trigonometri melalui Pendekatan Realistic Mathematics Education - Meika, Ika; Solikhah, E. Fidri Firdaushi; Yunitasari, Ika (Fakultas Keguruan dan Ilmu Pendidikan Universitas Singaperbangsa, 2023)
The purpose of this study was to develop teaching materials in the form of LKPD trigonometry materials through the RME approach. Research and development is carried out using the Design Based Research (DBR) method with the Plomp development model consisting of three stages, namely: Preliminary Research, Prototyping Stages and Assessment. This article is part of a research entitled